Hábitos de saúde, nível de atividade física, aspectos psicossociais e satisfação de usuários do Programa Academia da Saúde - Oliveira, André Moreira de (2023)
The Health Academy Program is a public initiative linked to Primary Care, Basic Health Units, Family Health Strategies and Expanded Family Health Centers, with an intersectoral, integrated and transversal relationship. By knowing the benefits of physical activity, good health and eating habits and the importance of evaluating public programs from the user's point of view, the aim of this study was to analyze health habits, level of physical activity, psychosocial aspects and user satisfaction of the Health Academy Program. Therefore, a cross-sectional descriptive correlational survey was carried out, with the data collection instrument being a specific questionnaire for Program users. The study included PAS users from three Regional Development Councils in the Rio Grande do Sul – Central, Jacuí Centro and Vale do Rio Pardo, totaling seven poles. The collected data were analyzed using descriptive statistics, with measures, standard deviations and percentages.